Eco‐Evolutionary Pathways Toward Industrial Cities. (1st March 2015) - Chandra‐Putra, Handi; Chen, Jing; Andrews, Clinton J.
Summary: Industrial location theory has not emphasized environmental concerns, and research on industrial symbiosis has not emphasized workforce housing concerns. This article brings jobs, housing, and environmental considerations together in an agent‐based model of industrial and household location. It shows that four classic outcomes emerge from the interplay of a relatively small number of explanatory factors: the isolated enterprise with commuters; the company town; the economic agglomeration; and the balanced city.